Antibacterial Effects of Recombinant Endolysins in Disinfecting Medical Equipment: A Pilot Study - Choi, Yoon-Jung; Kim, Shukho; Bae, Sohyun; Kim, Yoonjung; Chang, Hyun-Ha; Kim, Jungmin (Frontiers in Microbiology, 2022)
Nosocomial infections caused by multidrug-resistant (MDR) bacteria are severe life-threatening factors. Endolysins (lysins) degrade the bacterial cell wall peptidoglycan and may help control pathogens, especially MDR bacteria prevalent in hospital settings. This study was conducted to verify the potential of lysin as disinfectant to kill bacteria contaminating medical devices that cause hospital infections. Eight catheters removed from hospitalized patients were collected and tested for their ability to kill bacteria contaminating the catheters using two lysins, LysSS and CHAP-161. Catheter-contaminating bacterial species were isolated and identified by 16s rRNA sequencing. From the eight catheters, bacteria were cultured from seven catheters, and five bacterial species (Bacillus megaterium, Bacillus muralis, Corynebacterium striatum, Enterococcus faecium, and Staphylococcus epidermidis) were identified. LysSS could inhibit catheter-contaminating bacteria, including C. striatum and S. epidermidis, compared with untreated controls but could not inhibit the growth of E. faecium. CHAP-161 showed more bactericidal effects than LysSS, but could not inhibit the growth of S. epidermidis. C. striatum, E. faecium, and S. epidermidis. This study showed the potential of lysin as an alternative disinfectant for hazardous chemical disinfectants used in hospitals.